EFFECT OF PLASTICIZERS ON MECHANICAL PROPERTIES OF EDIBLE FILM FROM JANENG STARCH – CHITOSAN - Narlis Juandi; Rahmi Rahmi; Hira Helwati (Jurnal Natural, 2016)
The interest in the development of edible and biodegradable films has increased because it is every day more evident that non degradable are doing much damage to the environment. In this research, edible films were based on blends of janeng starch in different proportions, added of palm oil or glycerol, which were used as plasticizers. The objective was to study the effect of two different plasticizers, palm oil and glycerol of edible film from janeng starch–chitosan on the mechanical properties and FTIR spectra. Increasing concentration of glycerol as plasticizer resulted tend to increased tensile strength and elongation at break. The tensile strength and elongation at break values for palm oil is higher than glycerol as plasticizer at the same concentration. FTIR spectra show the process of making edible film from janeng starch–chitosan with palm oil or glycerol as plasticizers are physically mixing in the presence of hydrogen interactions between chains.